Parents Involvement in Early Childhood Education Institutions in Buleleng Regency, Bali - Magta, Mutiara; Handayani, Dewa Ayu Puteri (Universitas Negeri Semarang, 2019)
Parents are the first and the most important social environment in a child’s life. This study aimed at describing parents’ involvement at early childhood education institutions in Buleleng district, Buleleng regency, Bali. The data of the study were collected from 230 respondents at early childhood education institutions and were analyzed quantitatively and qualitatively. The results showed that most of the respondents had a tendency of a low involvement, i.e. , 136 respondents ( 59.1%) , while the number of respondents with a high involvement was 94 ( 49.9%). This indicates that there are still many parents who ignore the importance of parents’ role at school. In addition, the school has not yet got a program that maximally supports parents at school.